CONSCIENTIOUSNESS DAN AGREEABLENESS SEBAGAI PEMODERASI PENGARUH LOVE OF MONEY PADA TAX EVASION TENDENCY MAHASISWA MAGISTER AKUNTANSI - Kase, Marce Sherly; Suprasto, Herkulanus Bambang; Ratna Sari, Maria M. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.10.TAHUN 2017, 2017)
This study aims to test the moderating effect of conscientiousness and agreeableness in the relationship between love of money and  tax evasion tendency. The population in this study is graduate student of accounting of Udayana University. The sample selection method is nonprobability sampling with purposive sampling technique in order to obtain 85 people. Data were analyzed using Moderated Regression Analysis (MRA).  The result of regression analyses show that love of money is positively related to tax evasion tendency. Agreeableness is also found to moderate the relationship between love of money and tax evasion tendency but conscientiousness is not a moderator in this relationship.
Keywords: Love of Money, Tax Evasion Tendency, Conscientiousness, Agreeableness